Ewan - delos Santos, Christian V.
People nowadays seem to have this burning desire to be "different". It seems that they cannot stand to be just anybody, they have to be "extreme", and they have to be "individuals". For example, it is not a wonder why there is an abundance of "just do its", "express yourselves", "exhale your souls", and other mindless slogans? Why witchcraft is a fad? Are you not surprised at why Jolina Magdangal is famous? So, the question is, why, for all their efforts to be uniques individuals, why can't people just be themselves? In this generation, my generation, we are plagued by this lack of self-understanding, this lack of direction. It is common for us to haveve too much bravado that our youthfulness can justify. It is something very few of us escape or outgrow. In this generation where individuality seems to be of primary importance, I feel there is a need to let people know that they ought to understand themselves before they actually "dare to be themselves". Otherwise, our generation will never mature; we will just grow old. The story is about the importance of knowing who you are in the struggle for reaching one's ideals. The aim of this thesis is not to speak for this generation, but rather speak to it. This thesis desires to show us how and what this generation really is in the present state of things. As it is, we are becoming what is known by the standards of humanity as mediocre. We are labeled by society as apathetic, and the world considers us confused. Supposing this is a fair judgement of our character, maybe it is really time to do something about it. Maybe it is time for us to grow up.